Educating female adolescents against future proness to cancer disease (2007)
Cancer disease claimed 17.9 million lives of people in 1996, out of which 10.5 million were women of who had cancer either of the breast, cervix, uterus or ovary, arising from peoples engagement in attitudes that predispose them to the disease. The paper therefore stressed the need for female adolescents to be knowledgeable about cancer disease with reference to its types, cause and risk factors, signs and symptoms, preventive behaviour against cancer disease and the need to report themselves to a qualified doctor for early diagnosis and treatment on detection of any signs of cancer disease. The paper recommended that Ministries of Education at all levels should make health education a compulsory subject in secondary schools where students would be taught various health topics, including cancer disease. Health Education departments of Ministries of Health and non-governmental organisations should organise cancer education programmes at a regular interval' for secondary school students and the general public. This will reduce the morbidity and mortality rate arising from cancer disease.